The Existence of Sanghyang Jaran Dance in Pengubengan Temple - Ni Wayan Sugi Jutari; Ni Gusti Ayu Agung Nerawati (Jayapangus Press, 2023)
Sanghyang Jaran dance is one of the sacred dances in Bali. One of the sacred places in Bali that performs the dance is Pengubengan Temple. Sanghyang Jaran dance is performed twice a year during Tilem (III), namely during pujawali at Pengubengan Temple and tumpek wayang. The purpose of this research is to analyze the form of performance, function, and value of Hindu religious education in Sanghyang Jaran dance in Kutuh Village. The research data collection methods in this study are: observation, interview, literature study and documentation. The data that has been collected is analyzed using qualitative descriptive analysis method with steps, namely: Data reduction, Data Presentation, Conclusion Drawing and Data Verification; The results showed that: (1) The form of Sanghyang Jaran dance performance in Kutuh Village is to go through a series or procession of Sanghyang Jaran dance, namely nusdus, masolah, and ngalanus, and (2) The function of Sanghyang Jaran dance in Kutuh Village is: religious function, art and cultural preservation function, and social function. (3) The value of Hindu Education implied in the Sanghyang Jaran dance at Pengubengan Temple in Kutuh Village, namely: spiritual value and aesthetic value (Art).